2020
DOI: 10.3390/molecules25092173
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Extracting Solvents in the Recovery of Polyphenols from Green Tea and Its Antiradical Activity Supported by Principal Component Analysis

Abstract: Green tea contains a variety of biologically active constituents that are widely used in the pharmaceutical and food industries. Among them, simple catechins constitute a major group of compounds that is primarily responsible for the high biologic activity of green tea extracts. Therefore, the application of optimized extraction conditions may result in obtaining high value extracts. The main purpose of the study was to compare the content of polyphenols, mainly catechins, and the antioxidant activity of green… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…Koch et al. (2020) also reported that the use of methanol as a solvent resulted in a higher yield of bioactive components from green tea compared to water as a solvent. As methanolic GTE possessed high values of TPC, TFC and antioxidant activity than water GTE, it was further used for incorporation in starch polymer for the development of active packaging films.…”
Section: Resultsmentioning
confidence: 99%
“…Koch et al. (2020) also reported that the use of methanol as a solvent resulted in a higher yield of bioactive components from green tea compared to water as a solvent. As methanolic GTE possessed high values of TPC, TFC and antioxidant activity than water GTE, it was further used for incorporation in starch polymer for the development of active packaging films.…”
Section: Resultsmentioning
confidence: 99%
“…However, pressurized liquid extraction using methanol produced better recoveries of catechin (C) and epicatechin (EC) than water, ethanol, and ethyl acetate (Piñeiro et al., 2004). This indicates that ethyl acetate usage has a limitation depending on catechins of interest along with types and conditions of extraction methods (Koch et al., 2020). However, in this research, ethyl acetate is suggested to be the best solvent for isolating the catechin‐enriched fraction from CE by partitioning technique at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Green tea has well-known health benefits that have been attributed to its high content of antioxidant polyphenol catechins [33,34]. Hence, various methods for producing tea extracts with high levels of antioxidant activity and extractability have been attempted [35][36][37]. However, low bioavailability of green tea catechins limits the potential therapeutic benefits of green tea [18].…”
Section: Discussionmentioning
confidence: 99%